Potential For Marine Tourism Development in Kelapa Island, Thousand Islands, DKI Jakarta - Asep Parantika; Kelly Indah Sari (International Journal of Travel, Hospitality and Events, 2023)
Purpose: The study's objectives were to ascertain the current and potential circumstances on the island of Siput and the difficulties and possible strategies for promoting marine tourism there. Research methods: The researcher's qualitative method includes interviews, observation, and documentation. Data triangulation is the analytical approach employed. Result and discussion: The results show that Kelapa Island has advantages regarding uniqueness and beliefs held by individuals in the local community. The role of MSMEs around the island is also one of the advantages possessed by Kelapa Island. In addition, it was also found that the weakness of Kelapa Island is the need for more available funding for further development. While rivalry, egotism, and natural calamities pose challenges, Kelapa Island has the potential draws several businesses to invest there. The 4A (Attraction, Accessibility, Amenities, & Ancilliary) tourist development strategy for Kelapa Island has specific components that have been completed, beginning with attractions in the form of activities and cuisine. In contrast, amenities still need to be concentrated on restrooms and places of worship. Implication: This research can be used for further study, analyzing tourism and its development.   Keywords: Tourist Attractions, Marine, Tourism Development Strategy, Kelapa island